Impacts of Permafrost Degradation on Carbon Stocks and Emissions under a Warming Climate: A Review - Huijun Jin (MDPI AG, 2021)
A huge amount of carbon (C) is stored in permafrost regions. Climate warming and permafrost degradation induce gradual and abrupt carbon emissions into both the atmosphere and hydrosphere. In this paper, we review and synthesize recent advances in studies on carbon stocks in permafrost regions, biodegradability of permafrost organic carbon (POC), carbon emissions, and modeling/projecting permafrost carbon feedback to climate warming. The results showed that: (1) A large amount of organic carbon (1460–1600 PgC) is stored in permafrost regions, while there are large uncertainties in the estimation of carbon pools in subsea permafrost and in clathrates in terrestrial permafrost regions and offshore clathrate reservoirs; (2) many studies indicate that carbon pools in Circum-Arctic regions are on the rise despite the increasing release of POC under a warming climate, because of enhancing carbon uptake of boreal and arctic ecosystems; however, some ecosystem model studies indicate otherwise, that the permafrost carbon pool tends to decline as a result of conversion of permafrost regions from atmospheric sink to source under a warming climate; (3) multiple environmental factors affect the decomposability of POC, including ground hydrothermal regimes, carbon/nitrogen (C/N) ratio, organic carbon contents, and microbial communities, among others; and (4) however, results from modeling and projecting studies on the feedbacks of POC to climate warming indicate no conclusive or substantial acceleration of climate warming from POC emission and permafrost degradation over the 21st century. These projections may potentially underestimate the POC feedbacks to climate warming if abrupt POC emissions are not taken into account. We advise that studies on permafrost carbon feedbacks to climate warming should also focus more on the carbon feedbacks from the rapid permafrost degradation, such as thermokarst processes, gas hydrate destabilization, and wildfire-induced permafrost degradation. More attention should be paid to carbon emissions from aquatic systems because of their roles in channeling POC release and their significant methane release potentials.